2022
DOI: 10.1093/rb/rbac019
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-based metal organic framework with antibacterial and anti-inflammatory properties for promoting wound healing

Abstract: The synergistic effect of antibacterial and anti- inflammatory is needed to overcome the problem of wound healing difficulties. Based on the favorable antibacterial and anti- inflammatory effect of zinc ions (Zn2+) and the physicochemical properties of metal organic frameworks (MOFs), we prepared nanosized zinc-based MOF: Zn-BTC with the ability to slowly release Zn2+. In cellular levels, Zn-BTC possessed lower toxicity to fibroblasts and enhanced capacity of cell proliferation and migration. It also had good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 44 publications
(46 reference statements)
1
33
0
Order By: Relevance
“…193 Due to the bactericidal ability of metal ions such as Ag + , Zn 2+ , and Cu 2+ , NNPH with MOFs based nanomaterials serving nanofillers have also been studied for wound healing applications. [194][195][196] Deng et al reported an injectable biomimetic NNPH using metal-organic frameworks (MOFs) encapsulating with Au nanoparticles (Au@ZIF-8) and hydrogels prepared between carbohydrazidemodified GelMa and oxidized sodium alginate through Schiff-base as well as photo crosslinking. The NNPH displayed photodynamic bactericidal performance, with >99.0% of bacteria eradicated after light exposure (generating ROS) for 20 minutes.…”
Section: Metal-based Nanomaterials Of Nnphs For Wound Healingmentioning
confidence: 99%
“…193 Due to the bactericidal ability of metal ions such as Ag + , Zn 2+ , and Cu 2+ , NNPH with MOFs based nanomaterials serving nanofillers have also been studied for wound healing applications. [194][195][196] Deng et al reported an injectable biomimetic NNPH using metal-organic frameworks (MOFs) encapsulating with Au nanoparticles (Au@ZIF-8) and hydrogels prepared between carbohydrazidemodified GelMa and oxidized sodium alginate through Schiff-base as well as photo crosslinking. The NNPH displayed photodynamic bactericidal performance, with >99.0% of bacteria eradicated after light exposure (generating ROS) for 20 minutes.…”
Section: Metal-based Nanomaterials Of Nnphs For Wound Healingmentioning
confidence: 99%
“…For example, Gao et al . prepared nanosized zinc-based metal–organic frameworks (MOFs) with favorable antibacterial and anti-inflammatory properties via slowly releasing Zn ions [ 66 ]. Some metallic materials can be utilized in tumor ablation for their superior photothermal conversion efficiency [ 67 ].…”
Section: The Different Sources Of Biomaterials For Tissue Regenerationmentioning
confidence: 99%
“…Compared with traditional inorganic polymers (mesoporous silica) [ 112 , 113 ], hollow polymeric nanosphere (HPN) [ 114 ], porous organic polymers [ 115 ] (covalent organic frameworks (COF) [ 116 , 117 ], hypercrosslinked polymers (HCP) [ 118 ], inherently microporous polymers (PIM) [ 119 ], porous aromatic frameworks (PAF) [ 120 ], conjugated microporous polymers (CMP) [ 121 ], and other biodegradable polymers (polypeptides) [ 122 , 123 ], MOF-based composites offer great opportunities for multifunctionalization by virtue of their unique organic–inorganic hybrid composite structures, ordered porous structures, and high biocompatibility [ 124 ]. When dealing with complex wounds, MOFs can achieve wound healing effects by releasing metal ions and loading drugs, including regulating the oxidative stress response, antibacterial effects, and promoting angiogenesis, collagen deposition, and re-epithelialization [ 125 , 126 , 127 ], by improving wound site infection and blood flow reperfusion to accelerate the wound healing process and restore normal skin function ( Table 2 ).…”
Section: Application Of Mofs In Wound Healingmentioning
confidence: 99%